EFFICIENCY EVALUATION OF ACTIVITY OF THE RUSSIAN PUBLIC COMPANIES IN THE CONDITIONS OF ACTIVE REGULATION OF OPERATING COSTS AND EXTERNAL EFFECTS (SHOCKS) - S. I. Lutsenko (Стратегические решения и риск-менеджмент)
The author considers influences of active regulation of operating costs and negative effects (shocks) on financial policy of the Russian public companies. The Russian firms make the choice for benefit of internal financing for the purpose of increase in the corporate benefit in the conditions of external financial restrictions (sectoral sanctions). Growth of the corporate benefit leads to increment of company assets and respectively to welfare of the shareholder. The Russian public companies will review the capital structure in the conditions of growth of adjustment costs. The active policy of the Russian companies is connected with availability of sufficient size of assets which are source of mortgage providing for regulation of capital structure. Thereby, the organization solves problem of adverse selection – financing source selection taking into account its price. The companies are forced to regulate actively the capital structure in the conditions of growth of operating costs and negative shocks. Regulation of capital structure is connected with the aspiration of the company to keep part of debt for its use as financing source. Operating costs are the indicator estimating efficiency of management decisions. The Russian companies will finance the investments, first of all, by internal financing sources. Cash flows are the resource servicing the investment capital. The firms will be attracted the loan capital in the period of deficit of cash flow. The Russian companies will work in logic of precautionary motive, creating monetary stock in the conditions of shocks. The precautionary motive is the protective buffer from negative impacts from the capital markets. Low values of cash flows allow to limit the management concerning his illegal behavior – decision making in private interests.